UNIVERSAL PRIMERS AND FLUORESCENT PROBE DETECT REFERENCE 18S rRNA GENE IN ALL VERTEBRATES (Experimental biology, 2022)
Abstract: Detection of target genes via real-time PCR-based test-systems requires simultaneous detection of the internal control gene to avoid false negative results. Endogenous Internal Control genes (reference genes) have an advantage over the Exogenous Internal Controls (IC) as they are part of the cellular chromosomal DNA of an organism. Reference genes however have a disadvantage because they vary for each biological species causing additional development of primers and fluorescent probes for each separate biological species, which requires additional time and funds. In recent years, a significant number of studies are devoted to development of universal sets of primers / probes capable of detecting a reference gene in a wide range of biological objects – a whole class or even a living kingdom. Such universal sets of primers / probes will lead to unification of qPCR-based tests used in diagnostic purposes. This paper presents such a set for 18S rRNA reference gene determination in species included in the Vertebrata subtype. Using the developed set, the 18S rRNA gene was detected during the study in DNA samples of Mammals, Sauropsids, Amphibians, and Bony fishes; it showed 100% specificity. The set was also tested in different multiplex qPCR and kept specificity and sensitivity in tetraplex assay.
Keywords: Real-time PCR; 18S rRNA; reference gene; vertebrates; internal control gene